TRPA1-PI3K/Akt-OPA1-ferroptosis axis in ozone-induced bronchial epithelial cell and lung injury - Weng,J; Liu,Q; Li,C; Feng,Y; Chang,Q; Xie,M; Wang,X; Li,M; Zhang,H; Mao,R; Zhang,N; Yang,X; et al. (Science of the Total Environment, 2024)
BACKGROUND: Transient receptor potential (TRP) ankyrin 1 (TRPA1) could mediate ozone-induced lung injury. Optic Atrophy 1 (OPA1) is one of the significant mitochondrial fusion proteins. Impaired mitochondrial fusion, resulting in mitochondrial dysfunction and ferroptosis, may drive the onset and progression of lung injury. In this study, we examined whether TRPA1 mediated ozone-induced bronchial epithelial cell and lung injury by activating PI3K/Akt with the involvement of OPA1, leading to ferroptosis. METHODS: Wild-type, TRPA1-knockout (KO) mice (C57BL/6 J background) and ferrostatin-1 (Fer-1)-pretreated mice were exposed to 2.5 ppm ozone for 3 h. Human bronchial epithelial (BEAS-2B) cells were treated with 1 ppm ozone for 3 h in the presence of TRPA1 inhibitor A967079 or TRPA1-knockdown (KD) as well as pharmacological modulators of PI3K/Akt-OPA1-ferroptosis. Transcriptome was used to screen and decipher the differential gene expressions and pathways. Oxidative stress, inflammation and ferroptosis were measured together with mitochondrial morphology, function and dynamics. RESULTS: Acute ozone exposure induced airway inflammation and airway hyperresponsiveness (AHR), reduced mitochondrial fusion, and enhanced ferroptosis in mice. Similarly, acute ozone exposure induced inflammatory responses, altered redox responses, abnormal mitochondrial structure and function, reduced mitochondrial fusion and enhanced ferroptosis in BEAS-2B cells. There were increased mitochondrial fusion, reduced inflammatory responses, decreased redox responses and ferroptosis in ozone-exposed TRPA1-KO mice and Fer-1-pretreated ozone-exposed mice. A967079 and TRPA1-KD enhanced OPA1 and prevented ferroptosis through the PI3K/Akt pathway in BEAS-2B cells. These in vitro results were further confirmed in pharmacological modulator experiments. CONCLUSION: Exposure to ozone induces mitochondrial dysfunction in human bronchial epithelial cells and mouse lungs by activating T